(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
It is impossible to fully handle education in India without taking into account the country’s linguistic and cultural context. This main purpose of this paper is to provide background knowledge concerning India’s linguistic elements. The term "minorities" is considered in the context of India, and indeed the extra clothes by the Indian Constitution for minority communities is examined. Going to follow that, there is a consideration on language policy in Indian education, as well as an analysis of several college course ideas. Among the relevant areas explored are the variety of languages taught, the language of instruction, and curriculum design for residents of minority languages. The paper will also discuss several linguistic revolutions and their impact upon Indian education. Language is one of the most controversial subjects in Indian education. India, being a democratic, multilingual country and its educators are always discussing whether tongues should be exploited as a teaching medium, specifically for consumers of minority languages with no standard written forms.